Covid and Populism in the News: How Brazilian media outlets approach the issue of populism during the pandemic - Fernandes dos Santos, Nina; Moreira Cesar, Camila (Brazilian journalism research, 2021)
ABSTRACT – The recent rise of right-wing populism has given new momentum to the discussion about the meaning of populism around the world and the covid-19 pandemic added yet another layer to the issue. Considering the growing circulation of the term “populism” in public discourse, as well as the volatility of its meaning, this paper seeks to identify the different constructions of meaning around this phenomenon by Brazilian media during the covid-19 pandemic. Through quantitative and qualitative analysis, in which we used the perspective of media framings, we examine 170 articles from 17 Brazilian media outlets published between March 1st and October 1st, 2020. The results allow us to conclude that there are circumstantial meanings of populism that were incorporated during the pandemic, especially related to an antiscientific approach. RESUMO – A recente ascensão do populismo de direita tem dado um novo impulso à discussão sobre o significado do populismo em todo o mundo e a pandemia da covid-19 acrescentou uma camada complementar à questão. Considerando a crescente circulação do termo “populismo” no discurso público, bem como a volatilidade de seu significado, este artigo busca identificar as diferentes construções de sentido em torno deste fenômeno nos meios de comunicação brasileiros durante a pandemia da covid-19. Por meio de análises quantitativas e qualitativas, nas quais mobilizamos a perspectiva dos enquadramentos midiáticos, examinamos 170 artigos de 17 veículos de comunicação brasileiros publicados entre 1º de março e 1º de outubro de 2020. Os resultados permitem concluir que há sentidos circunstanciais do populismo que são incorporados durante a pandemia, especialmente relacionados a uma abordagem anticientífica RESUMEN – El reciente aumento del populismo de derecha ha dado un nuevo impulso a la discusión sobre el significado del populismo en todo el mundo y la pandemia de covid-19 agregó una capa más al problema. Considerando la creciente circulación del término “populismo” en el discurso público, así como la volatilidad de su significado, este trabajo busca identificar las diferentes construcciones de significado en torno al fenómeno por los medios brasileños durante la pandemia de covid-19. A través de un análisis cuantitativo y cualitativo, en el que utilizamos la perspectiva de los encuadres mediáticos, examinamos 170 artículos de 17 medios brasileños publicados entre el 1 de marzo y el 1 de octubre de 2020. Los resultados brindan elementos que nos permiten concluir que durante la pandemia se incorporaron significados circunstanciales del populismo, especialmente relacionados con un enfoque anticientífico.